Impact of Oral Probiotics on Faecal Profile in Endangered Asian Elephant (Elephas maximus) - Chharang, Dharmendra; Choudhary, Sheela; Rathore, Bhavana; Chopra, Deepak; Meena, Kavita (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A study was planned to determine the impact of oral probiotics on faecal profiles in 18 adult Asian elephants (Elephas maximus) for sixty days. The elephants were randomly divided into three groups, with six each. The experimental probiotics; Lactobacillus acidophilus and Saccharomyces cerevisiae, were supplemented @ 1 gm (1 × 109 cfu /gm) / 50 kg body weight per day to all the elephants of T2 and T3 groups, respectively, whereas no probiotic was given to the control (T1) group. The faecal samples were taken on 0 and 60th day of the experiment for the analysis of faecal profiles viz. pH, lactic acid, coliforms, and probiotic microbial counts, i.e., lactobacillus and mould. Oral feeding of probiotics did not exhibit any significant impact on faecal profiles; however, it seems to induce some shift in faecal microflora. A declining trend in lactobacillus count was observed in probiotic groups as compared to the control group, which could be implicative of positive health status in Asian elephants.
Keywords: Asian elephants; Faecal profiles; Lactobacillus; Mould; Probiotics